Students’ Perception of using Weekly Quizzes in EFL Classroom - Geminastiti Sakkir; Nur Safitri S; Maemuna Muhayyang (Celebes Journal of Language Studies, 2022)
The purpose of this study is to discuss and discover how students feel about using weekly quizzes in an EFL classroom. This research used mixed methods (QUAL-Quan). The population of in this study was the 3rd year students of the English Education Study Program at Universitas Negeri Makassar. Cluster random sampling was used to choose the 45 students for this study. The research used observation, interview, and a questionnaire as instruments. As a result, the students' perceptions of the utilization of weekly quizzes reflect this research. The result of the research showed that the students showed that students' perception of using weekly quizzes in EFL classroom in a positive category. According to the results of the research, it can be concluded that the use of weekly quizzes in EFL classroom can be a tool to determine and measure students' understanding of the material that has been taught previously.